Zodiacal exoplanets in time – XIII. Planet orbits and atmospheres in the V1298 Tau system, a keystone in studies of early planetary evolution. Issue 2 (28th October 2021) - Gaidos, E; Hirano, T; Beichman, C; Livingston, J; Harakawa, H; Hodapp, K W; Ishizuka, M; Jacobson, S; Konishi, M; Kotani, T; Kudo, T; Kurokawa, T; et al.
ABSTRACT: Studies of planetary systems of stars in star-forming regions and young clusters open a window on the formative stages of planetary evolution. We obtained high-cadence high-resolution infrared spectroscopy of the solar-mass Taurus association-member V1298 Tau during a transit of its 10R⊕ -size 'b' planet. We measured the systemic radial velocity (RV) and find that the kinematics of V1298 Tau suggest an affiliation with a ≳6 Myr-old subgroup. A comparison of V1298 Tau and the nearby, co-moving star 2M0405 with stellar evolution models suggests an age of ∼10–25 Myr. We measured the projected spin-orbit angle of 'b' as λ =15_-16^+15 and λ = 2_-4^+12 degrees using the apparent RV shift and change in line profile, respectively, induced by the transient occultation of the rotating star by the planet. These values indicate a prograde orbit like that of the interior 'c' planet of V1298 Tau and point to a co-planar multiplanet system that formed within a disc. We also measured variation in the strength of the 1083 nm triplet of neutral orthohelium as a probe of any extended/escaping atmosphere around 'b'. We detect a steady decrease in absorption over the transit that appears to arise from the star or its planetary system. While this variation could be ascribed to 'b' or possibly to the immediately preceding transit of 'd', we cannot rule out that this is due to rapid variation in the stellar disc-integrated flux in the triplet. The amplitude of variation (∼0.04 nm) is consistent with moderate estimates of atmospheric escape driven by XUV radiation from the central star.